Students’ Voice Toward English for Nutritionist and Dietitian - Dewintha, Rezza; Trihardiani, Ismi (English Department FBS UNP, 2024)
This paper addressed the students’ voice toward English for Nutritionist and Dietitians. Its objective was to know the holistic experience of learning during ESP material given to them. This study used a diary circle combining online diary method with face-to-face focus group to generate dialogue. Data analysed narratively in form of descriptive data in nature. Researcher did believe students faced some problems in learning English, furthermore they were not an English major student. They got English especially as additional competence to support their main role as health workers. The poor internet connection while teaching learning process. Furthermore, the results of this study showed that 85.2% students were excited in English Class, 72.2% were focused, 60% were participated, 68.7% were interested, 53.9% like group discussion a lot, 40.9% gave intentions to listening skill, 43.5% liked poster as one of the assignments, 50.4% were asked their friend to have discussion, 73.9% said that English class was easy but still they need help, and 64.3% students were very happy. This study leaded to get the emotional dimensions of learning method and of course can be applied in teaching approach.